Pengaruh Promosi dan Layanan Shopee Paylater terhadap Pembelian Impulsif pada Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung - Dewantara, Yoga Reky; Hastuti, Maria Agatha Sri Widyanti (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to determine: 1) the influence of promotions on impulsive buying behavior, and 2) the influence of Shopee PayLater services on impulsive buying behavior among students. This research is quantitative in nature. The population in this study consists of 90 VIII semester students of the Economics Education Study Program at Universitas Bhinneka PGRI Tulungagung, using a saturated sampling method. Data collection was carried out using a questionnaire. The analysis results show: 1) partially, the t value is greater than the t table value (13.856 > 1.987) and the significance value is less than 0.05 (0.000 < 0.05), indicating that promotions have a significant effect on impulsive buying behavior. 2) partially, the t value is greater than the t table value (2.039 > 1.987) and the significance value is less than 0.05 (0.044 < 0.05), indicating that Shopee PayLater services have a significant effect on impulsive buying behavior. 3) simultaneously, the F value is greater than the F table value (113.466 > 3.95) and the significance value is 0.000 < 0.05. The Adjusted R² value of 71.6% indicates that impulsive buying behavior is influenced by promotions and Shopee PayLater services, while the remaining 28.4% is influenced by other variables not examined in this study.